ANALYSIS OF PROCEDURES FOR COLLECTING, DEPOSITING, AND REPORTING INCOME TAX ARTICLE 22 BY THE REGIONAL GENERAL TREASURER AT THE REGIONAL FINANCE AND ASSET AGENCY OF SERUYAN REGENCY - Rampai, Eltridea Ivana; Kasno, Kasno (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The procedures for collecting, depositing, and reporting Income Tax (PPh) Article 22 by local government treasurers have a strategic role in maintaining tax compliance and supporting the optimisation of state revenue. This study aims to analyse the implementation of Income Tax Article 22 by the Regional General Treasurer at the Regional Finance and Assets Agency of Seruyan Regency. The research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results showed that although the collection and deposit procedures were in accordance with the provisions, there were still weaknesses in reporting such as delays in filling out tax returns and technical errors. The process of depositing and reporting has switched to a Coretax-based digital system developed by the Directorate General of Taxes, but its implementation still faces obstacles in the form of limited digital literacy and human resource readiness. Therefore, there is a need to increase human resource capacity and strengthen the electronic-based reporting system to ensure tax accuracy and compliance on an ongoing basis.